2018
DOI: 10.1111/bju.14198
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility of intestinal Escherichia coli in men undergoing transrectal prostate biopsies: a prospective, registered, multicentre study

Abstract: The occurrence of intestinal FQ-R and/or 3GC-R (potentially ESBL-producing) E. coli strains in men undergoing TRUS-Bx in Finland is notable. The finding is consistent with the global increase in antimicrobial resistance. International travel appears to be an indisputable risk factor for having intestinal FQ-R E. coli strains. The contemporary antimicrobial resistance situation should be taken into account in the care of post-TRUS-Bx infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
12
1
Order By: Relevance
“…Our ESBL prevalence was quite low when compared with neighbouring countries . A recent study from Finland also discovered much higher rates of resistant organisms . It has previously been shown that ESBL rates vary widely among countries.…”
Section: Discussioncontrasting
confidence: 40%
“…Our ESBL prevalence was quite low when compared with neighbouring countries . A recent study from Finland also discovered much higher rates of resistant organisms . It has previously been shown that ESBL rates vary widely among countries.…”
Section: Discussioncontrasting
confidence: 40%
“…12,13 Cases of ESBL-producing E. coli bacteraemia have been reported after prostate biopsies 17 and international travel has been identified as the risk factor for fluoroquinolone-resistant and ESBL-producing E. coli infections. 16,61 Therefore, the role of screening and contact precaution of returned travellers from clinical and public health perspectives need to be further examined. 62 It is unfeasible to screen all returning travellers, but in a healthcare setting, it may be feasible to screen those who are planning to undergo higher risk medical procedures; although current evidence suggest that ESBL- producing E. coli is less likely to spread between patients in hospitals than other Enterobacterales species.…”
Section: Acute Diarrhoea Is the Most Common Condition Affecting Travementioning
confidence: 99%
“…All prostate biopsies were performed transrectally by experienced urologists ( n = 7) without enema and with periprostatic block. Antibiotic prophylaxis and biopsy-related complications have been recently reported [18,19]. For each man with at least 1 IMPROD Likert score 3–5 lesion, the biopsy procedure started with a TB.…”
Section: Methodsmentioning
confidence: 99%